Impact of Digital Transformation on International Trade - Cai, Yajing; Zhang, Wanchen; Kong, Linkai; Yang, Yunji; Yang, Zhengyuanyi (Transactions on Economics, Business and Management Research, 2024)
Digital transformation is profoundly affecting international trade, bringing both positive impacts and challenges; digitization and automation of trade processes have increased efficiency and reduced costs; cross-border trade facilitation has promoted global business exchanges; and data-driven decision-making has optimized market operations; however, issues such as the aggravation of the digital divide, data security and privacy protection, and barriers to the application of emerging technologies also need to be addressed, with corresponding measures and recommendations in the areas of policy, technology, and infrastructure development, and other corresponding measures and recommendations were put forward to promote digital transformation and the healthy development of international trade.